P1134Cardiac pacemakers and transient electromagnetic interferences during radiotherapy courses: a multicentre, real-time, in-vitro evaluation. (18th June 2020) - Di Girolamo, E; Appignani, M; Marini, M; De Filippo, P; Leidi, C; Di Girolamo, F; Delana, A; Barbareschi, A; Andreoli, S; Genovesi, D; Falco, M D
Abstract: Funding Acknowledgements: None Background: The effects of high dose oncologic radiotherapy (RT) on cardiac pacemakers (PMs), at even less than 6 MV power, are unpredictable, depending on multiple factors. Normal PM function may be impaired during direct exposure, due to electromagnetic interferences (EMIs). Potentially life-threatening malfunctions may occur, expecially in PM-dependent patients, and both manufacturers and guidelines discourage direct exposure. Purpose: To evaluate transient EMI-related PM malfunctions during direct exposure to doses up to 10 Gy during radiotherapy course, 17 wireless-telemetry-enabled PMs with sufficient residual battery charge for the purpose of the study (at least 4 months to elective replacement indicator, E.R.I.) were evaluated in three different centres. Methods: All PMs underwent baseline interrogation. Single chamber devices were programmed in the VVI/40 mode while dual or triple chamber devices were programmed in the DDD/40 mode. To avoid the "run-away" phenomenon during exposure rate-adaptive function was disabled. A centering computed tomography was performed to build the corresponding treatment plan and the PMs were blinded randomized to receive either 2, 5 or 10 Gy exposure by a 6 MV linear accelerator in a homemade water phantom (600 Um/min). The effective dose received by the PMs was randomly assessed by an in-vivo dosimetry. During RT course, the devices were observed in a real-time session using manufacturer specific equipment, and PM function (pacing and sensing, programmed parameters) was recorder by a video camera in the bunker throughout the entire radiation exposure. Results: During RT course, 13 PMs (76.5%) recorded not clinically relevant minor transient  EMIs, and no atrial and/or ventricular oversensing nor base-rate-pacing inhibition were observed. Only 4 PMs (23.5%) reported neither transient malfunction nor minor EMIs, withstanding direct radiation exposure. Transient EMI-related malfunctions were observed regardless of either 2, 5 or 10 Gy exposure. Conclusions: Minor, not clinically relevant EMI-related interferences were observed in most of the PMs during direct exposure. Nevertheless, to avoid potentially life-threatening PM malfunctions, magnet application on the PM pocket site or reprogramming are still suggested in PM-dependent (high risk) patients ongoing even low energy RT exposure.